Atmospheric and crosstalk corrections in Aster data for the mapping of soil mineralogical relationship - Baptista, Gustavo Macedo de Mello; Vivaldi, Daniella Dias; Meneses, Paulo Roberto (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of atmospheric and crosstalk (the electrical or optical signals of band leaks into another band) corrections of RCGbscale image quality, in Aster SWIR data, on the identification of the mineralogical relationship RCGb [kaolinite/(kaolinite + gibbsite)], in a spot of bare soils derived from the Niquelândia Complex, composed by gabbronorites, norites and pyroxenites. Raw data were used for L1A, L1B (radiance at the top of the atmosphere), AST07 (surface reflectance without crosstalk correction) and AST07XT (surface reflectance with crosstalk correction) on-demand products, the atmospheric correction modules Flaash and Quac, and the CRSTK30 crosstalk correction program. The results were sorted according to the following parameters: the transects RCGbscale and RCGbATG; the identification of the spatialization of the mineralogical relationship in the RCGbscale images, which were sliced into Ki value classes; and the quantitative check of the similarity degree between the values of 17 points of the RCGbscale and RCGbATG transects, by Student’s t and Mann-Whitney U statistical tests. The procedures showed 75% satisfactory results for the proposed study. The L1B data, as well as the atmospheric and crosstalk effects, do not interfere in the identification of the RCGb relationship. Studies in other soils should be stimulated for a better understanding of the interference of these corrections in Aster data.